Technology foresight for AI-based Continuing Professional Development (CPD) accreditation system insights from licensed chemists in the Philippines - Micosa, Bianca (University of the Philippines Diliman, 2025)
AI integration in the PRCs CPD accreditation system could pave the way towards better system enhancements and a better learning management system. This study focused on the future of an AI-based CPD accreditation system through insights from licensed chemists and CPD providers through a technology foresight framework in scenario building. The study has provided three possible scenarios, accompanied by key predictable variables and critical uncertainties that need to be considered for AI integration. The study has identified that while licensed chemists had inclination to adopt an AI-based system, they demand more detailed AI regulations, system enhancements, and security measures in place. Other key drivers were also noted such as the need for unification of accurate data within PRC's systems, their technological readiness, government initiatives, and presence of energy constraints. The strategies formulated to combat challenges were centered on sufficient technological planning, catching up, sustainable planning, and enhancement of public trust by ensuring safe usage of AI.